A 24‐GHz active up/down bidirectional mixer in 130‐nm RF CMOS. Issue 6 (26th February 2022) - Cao, Qingshan; He, Jin; Ji, Zhongling; Deng, Dongqing; Wang, Hao; Chang, Sheng; Huang, Qijun; Li, Jiankang
Abstract: An active bidirectional mixer based on modified Gilbert cell has been proposed to perform the up/down conversion at 24 GHz in a 130‐nm RF CMOS. Employing the transconductance g m /load sharing stage, the mixer not only reduces the required power of local oscillator (LO) signal, but also increases the linearity and the conversion gain (CG). With a 2‐dBm LO power, the mixer achieves measured CG of −1.7 dB, noise figure (NF) of 14.6 dB, and output 1‐dB compression point (OP1dB ) of −8.4 dBm at 24 GHz in the up‐conversion mode. In the down‐conversion mode, the mixer exhibits measured CG of 2.6 dB, NF of 15.9 dB, and input 1‐dB compression point (IP1dB ) of −0.1 dBm at 24 GHz. From 23 to 25 GHz, the measured LO‐to‐RF and LO‐to‐IF isolations (ISOs) are better than 55 dB and 48 dB, respectively. The chip area including all testing pads is 0.75 × 0.8 mm 2, which consumes 10.5 mW from a supply of 1.5 V.